Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1651-2227.1994.tb13128.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐genetic risk determinants for type 1 (insulin‐dependent) diabetes mellitus in childhood

Abstract: Using the prospective Hungarian childhood diabetes register, a nationwide case-control study was carried out to investigate the possible role of various non-genetic factors as risk determinants for type 1 diabetes in childhood. A questionnaire (covering family characteristics, social status, fetal and perinatal events, breast-feeding habits, infectious diseases and stressful life events) was sent by mail to all incident diabetic children in 1990 (n = 163) and to two referent children (for each diabetic child),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2
7

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 24 publications
(20 reference statements)
7
48
2
7
Order By: Relevance
“…The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Three articles [25,26,28] reported the same data. A study [33] was excluded because no raw data were presented in the paper or available from the authors. Another study was excluded as it contained fewer than 15 cases [29].…”
Section: Resultsmentioning
confidence: 99%
“…A study from Denmark (with 839 cases) reported no significant difference in birthweight between cases and controls. Finally, two other studies, one from Hungary [29] and one from USA [40], reported little evidence of a difference, but contained relatively few cases (163 and 103, respectively). …”
Section: )mentioning
confidence: 94%
“…For instance, per 500 g increase in birthweight, there was a 4% (OR Other studies In five of the studies identified by our searches [29,30,33,35,40] the required data could not be obtained from authors (or extracted from the published reports). In a Swedish study [30] (with 4,584 cases of type 1 diabetes) we were able to estimate results from a figure, but only using a different reference category (of 3.0 to 4.0 kg).…”
Section: Adjustments For Potential Confoundersmentioning
confidence: 99%
“…In Germany, as in other European countries, the growing social inequality among children is a serious problem [6]. Epidemiological studies on the association between social status and type 1 diabetes in children have reported conflicting results, finding positive [7][8][9][10][11][12][13][14][15][16][17], inverse [18][19][20][21][22][23][24][25] or no associations [26][27][28]. Likewise, the results of studies on the relation with population density and with urban versus rural areas are contradictory [10,13,14,17,19,29,30].…”
Section: Introductionmentioning
confidence: 99%